MicroRNA-16-1-3p Represses Breast Tumor Growth and Metastasis by Inhibiting PGK1-Mediated Warburg Effect - Ye, Tianxing; Liang, Yingchun; Zhang, Deyu; Zhang, Xuewu (Frontiers in Cell and Developmental Biology, 2020)
The Warburg effect (aerobic glycolysis) is a hallmark of cancer and is becoming a promising target for diagnosis and therapy. Phosphoglycerate kinase 1 (PGK1) is the first ATP-generating glycolytic enzyme in the aerobic glycolysis pathway and plays an important role in cancer development and progression. However, how microRNAs (miRNAs) regulate PGK1-mediated aerobic glycolysis remains unknown. Here, we show that miR-16-1-3p inhibits PGK1 expression by directly targeting its 3’-untranslated region. Through inhibition of PGK1, miR-16-1-3p suppressed aerobic glycolysis by decreasing glucose uptake, lactate and ATP production, and extracellular acidification rate, and increasing oxygen consumption rate in breast cancer cells. Aerobic glycolysis regulated by the miR-16-1-3p/PGK1 axis is critical for modulating breast cancer cell proliferation, migration, invasion and metastasis in vitro and in vivo. In breast cancer patients, miR-16-1-3p expression is negatively correlated with PGK1 expression and breast cancer lung metastasis. Our findings provide clues regarding the role of miR-16-1-3p as a tumor suppressor in breast cancer through PGK1 suppression. Targeting PGK1 through miR-16-1-3p could be a promising strategy for breast cancer therapy.